Virtual Teaching as a Mode of Undergraduate Medical Education during Covid 19 Pandemic: Its Effectiveness, Facilitators and Barriers for Medical Education- A Survey-Based Observational Study. - Ankur Dharmani; Jiya Lal (Pediatric Review: International Journal of Pediatric Research, 2021)
Objective: To evaluate the effectiveness, facilitators and barriers of online teaching of undergraduate medical students during the covid 19 pandemic. Methods: This google survey was conducted at a tertiary health care institute (Dr Yashwant Singh Parmar Government Medical College Nahan, Himachal Pradesh) of North India in August 2020. MBBS students of 4th and 5th year participated in the study. The questionnaire prepared on Google Forms (Google LLC, Mountain View, CA, USA) was organized in five sections, namely: E-learning, Web Quality, Technology, Teaching Sessions and Management Support. This was shared with the students with a link. Students’ participation was voluntary, anonymous and without any fear or reward. Results: About 41.6% (77) students were already familiar with it. Time flexibility was reported as a significant advantage by 48.1% (89), and network connectivity an important limitation by 44.9% (83). 60.5% (112) wanted post-pandemic in-person teaching.18.9% faced technical difficulty due to devices and gadgets. 44.9% (83) suggested chatbox use for interaction to enhance clinical skills, 60.5% (112) opined videos demonstration, 31.9% (59) suggested sharing of the study material in advance, and 97.3% (180) opted for post-pandemic clinical catch-up classes to supplement its effectiveness. For Management support, 28.1% (52) opined for institutional policy, 27.6% (51) reported infrastructure inadequacy for providing online medical education and technical support was a concern for 18.4% (34). 88.6% (164) favoured establishing a medical digital library to access medical literature. Conclusion: This study picks up a few gaps in online teaching. Addressing these gaps will make it more meaningful and a step forward to meet the objectives of medical education.